An Improved Approach of Digital Watermarking in Frequency Domain (International Journal of Engineering and Computer Science, 2014)
Digital watermarking is the processing of combined information into a digital signal. A watermark is a secondary image, which is overlaid on the host image, and provides a means of protecting the image. It acts as a digital signature, giving the image a sense of ownership or authenticity. Digital watermarking technique is very impressive for image authentication or protection for attacks. This paperproposes an approach to robust digital watermarking in frequency domain.  The approach is divided in two parts: one is watermark embedding and another is watermark extraction.  For watermarking SWT transformation is performed. MSE and PSNR are calculated for the extracted watermark.The robustness of different digital watermarking algorithms in frequency domain is evaluated by applying different attacks and by calculating PSNR. In this paper comparison is also performed between the proposed technique and DCT, DFT and DWT.